(untitled) (International Journal of Physiotherapy, 2023)
Background: Stroke causes a variety of impairments that compromise the quality of life. Constraint Induced Movement Therapy (CIMT) is a technique used in rehabilitation medicine to treat individuals with decreased upper extremity functions. The study compares the effectiveness of modified constraint-induced movement therapy (mCIMT), proprioceptive training, and task-oriented training on upper extremity functions among stroke patients. Methods: This study was an experimental study of pre and post-type. The study was carried out in ACS Medical College and Hospital, Chennai. Sixty male and female samples from the stroke population were selected and allocated to three groups by random sampling method. Group A, B & C were allocated with twenty samples in each group. The study duration was six months with an intervention duration of 30 minutes per day/alternate days of a week for four weeks. The FMA-UE and Motor Activity Log assessed upper extremity function and pain as the main outcome measures. Dependent t-tests were used to find out the effects within the group. ANOVA was used to compare the effectiveness between the groups. Results: Comparative study between Groups A, Group B, Group C showed a significant difference in the effectiveness of Motor Function, Sensory Function, ROM, Joint Pain, Muscle use, and Quality of Movement with a P value of 0.0001 on functions of upper extremity among stroke patients. Conclusion: The study concluded that modified constraint-induced movement therapy got more improvement than proprioceptive and task-oriented training on upper extremity functions among stroke patients.